Growth and physiological responses of enset (Ensete ventricosum) clones induced by a leaf extract and infected with Xanthomonas campestris pv musacearum, causal agent of bacterial wilt - Getahun Yemata; Masresha Fetene (Journal of the Saudi Society of Agricultural Sciences)
Enset (Ensete ventricosum (Welw.) Cheesman is a multi-purpose crop widely cultivated in the south and southwestern Ethiopia. It supports the livelihood of approximately 20 million people. However, the cultivation of the crop is impeded by enset bacterial wilt disease caused by Xanthomonas campestris pv musacearum (Xcm). The objective of the study was to evaluate the role of induction with a leaf extract in ameliorating the performance of infected enset clones and the subsequent effect on disease incidence reduction under field condition. Photosynthetic assimilation rate was measured using LCPro+ portable photosynthesis system. Disease incidence was determined by dividing number of dead plants to total number of plants inoculated and multiplied by 100. Infection affected the growth and physiology of both clones where more damage was noted in the susceptible clone. Infected plants of this clone showed a significant decrease in plant height (PH), pseudostem girth (PSG) and leaf area index (LAI) as compared to controls. However, induction brought 21.4, 25, 46 and 46% increment in PH, PSG, total leaf area and LAI, respectively, as compared to infected controls at 9 months after treatment (9 MAT). Similarly, induction improved the photosynthetic assimilation rate of the susceptible clone. There was a significant variation in disease incidence between treatments and clones. The highest disease incidence was recorded in infected control plants of the susceptible clone. Induction reduced disease incidence by 33.5 and 10.6% in the susceptible and resistant clones, respectively, as compared to infected controls. This shows that systemic acquired resistance could be used as an alternative tool to control enset bacterial wilt. However, further researches should be conducted under different agroecologies to draw a conclusive recommendation. Keywords: Assimilation rate, Disease incidence, Ensete ventricosum, Resistance induction, Pseudostem girth